Efeitos do treinamento de memória autobiográfica em indivíduos com doença de alzheimer: uma revisão sistemática - Conserva, Gabriella Nayara Siqueira de Lima (2021)
Introduction: Alzheimer's disease is characterized by the decline of cognitive functions, including autobiographical memory and, consequently, the sense of identity. Studies show that autobiographical memory training (TrMA) favors autobiographical recall in this population, however, to date, no study has reviewed the literature in order to identify the effectiveness of TrMA, so this systematic review aims to synthesize the literature and to evaluate the effect of TrMA in the evocation of personal memories of elderly people with Alzheimer's disease. Methods: PubMed, The Cochrane Library, Scopus and PsycInfo and Google Scholar databases were searched until April 2021, with no restriction on language and publication date. Regarding the methodology design, randomized clinical trials (controlled or uncontrolled), non randomized clinical trials, pilot studies and quasi-experimental studies were included. The search strategy was developed based on the Medical Subject Headings (MeSH) vocabulary descriptors, being adjusted according to the terminology used by each database. Results: The search generated 521 articles, among which 34 were selected and 5 were included. Overall, the results of the studies point to beneficial and statistically significant effects on autobiographical recall in response to the application of TrMA, except in one study, whose difference between the treatment group and the control group was not significant, despite the percentage of reported memories were higher in the treatment group. Discussion: The findings point to autobiographical memory training as a promising intervention regarding the preservation of personal memories and, consequently, the maintenance of the sense of identity in individuals with Alzheimer's for as long as possible. However, they must be interpreted with caution, as the studies found consist of evidence with an overall presence of high risk of bias. Final considerations: Currently, research on the effectiveness of autobiographical memory training is at an early stage, with a small number of studies that met the inclusion criteria, which does not allow firm conclusions to be drawn about its effectiveness. However, the evidence found indicates that the implementation of training in AD is a potential field.